Eksistensi Lembaga Kependidikan Islam di Indonesia - Fuad, Mochamad (Unisia, 2016)
The existence of institutions of Islamic education in Indonesia has been progressing. The progress has been cultural adaptation in response development and social change process without loosing their Islamic essence. Islamic society in Indonesia has agreed that Islamic education are part of Islamic life system, namely the process of intemalization and socialization of Islamic moral values through information or knowledge, attitude, behaviour, and culture to resolve their problems of life, to sustain their life, and to improve quality of life of students and youth generation. Regeneration and development of Islamic education institutions have brought changes to three problems of education, namely fundamental, structural, and operational problems, and will be able to respond problems of education at present.